2015
DOI: 10.1007/s40094-015-0177-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate temperature on ZnS films prepared by thermal evaporation technique

Abstract: The nanocrystalline ZnS semiconducting thin films of 500 nm thickness have been deposited on glass substrate at different substrate temperatures (T s ) by thermal evaporation technique. The structural property of deposited thin films has been measured by X-ray diffraction, scanning electron microscopy, and Energy dispersive analysis of X-ray. The electrical and optical properties of thin films have been determined by D.C. two point probe and ultraviolet visible spectroscopy measurements. The X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 21 publications
(18 reference statements)
2
15
0
Order By: Relevance
“…Our results showed that increased crystallite size led to reduction in dislocation density and subsequent reduction in grain boundary. Similar findings were reported by Vishwakarma [40] and Nwofe et al [41]. The good crystallinity and large crystallite size obtained in ZnS(C) is a reflection of the strong and sharp intensity peak [42] which is due to the low temperature condition during synthesis.…”
Section: X-ray Diffraction Analysis Of Zns Samplessupporting
confidence: 87%
“…Our results showed that increased crystallite size led to reduction in dislocation density and subsequent reduction in grain boundary. Similar findings were reported by Vishwakarma [40] and Nwofe et al [41]. The good crystallinity and large crystallite size obtained in ZnS(C) is a reflection of the strong and sharp intensity peak [42] which is due to the low temperature condition during synthesis.…”
Section: X-ray Diffraction Analysis Of Zns Samplessupporting
confidence: 87%
“…The activation energy, electrical resistivity and conductivity of all ZnS thin films were determined using the twopoint probe method. The relation for resistivity with temperature is denoted by [30]: where ρ is resistivity (in Ω•cm), E a is activation energy (in eV), k B is Boltzmann constant (in eV/K), T is the temperature (in Kelvin) and log C is constant. The Hall coefficient, carrier concentration and mobility of thin films were figured out using the relation given below [31]:…”
Section: Electrical Measurementsmentioning
confidence: 99%
“…There are various means suggested by researchers for substrate cleaning and documented in literature [33][34][35][36][37]. The most common includes glass substrate boiled in chromic acid for ~2 hr and kept in it for 12 hr.…”
Section: Substrate Cleaningmentioning
confidence: 99%